Mechanical properties of laser beam welded Ti6Al4V - Fan, Yu (2010)
Many items of medical, aeronautical, electronic and military equipment exposed to corrosive conditions, or required to have extreme performance characteristics, are sealed hermetically into micro packages. Laser beam welded (LBW) Ti6AI4V alloy has been adopted in anti-corrosion micro packages for the impeller of a left ventricular assistance device (LVAD). Thin and narrow welds were required for such medical equipment. A wide variety of laser types can be applied in sealing micro packages, which include traditional lasers (CO2, Diode and Nd: YAG) to the newest laser types (fibre). Compared with other LBW types, continuous wave fibre laser welds are well known for exhibiting narrow weld zones, low distortion, lower heat input and high efficiency. However, in this work significant porosity was found in the continuous wave fibre laser welds due to the high traverse speeds and high associated solidification rates. The largest distortion and melting area was found in the continuous wave diode laser welds due to the high heat generation. A pulsed Nd: YAG welding was suggested as the hermetic laser welding technique for sealing the micro packages, since it is a good-balance between low porosity, less distortion and a narrow weld zone. The microstructures of Ti6AI4V were complex and strongly affected the mechanical properties. These structures include: a' martensite, metastable ß, Widmanstätten, bimodal, lamellar and equiaxed microstructure. Bimodal and Widmanstätten structures exhibit a good-balance between strength and ductility. The microstructure of laser beam welded Ti6AI4V was primarily a' martensite, which showed the lowest ductility but not significantly high strength. A heat treatment at 950°C followed by furnace cooling can transform the microstructure in the weld from a' martensite structure into Widmanstätten structure. The fatigue fracture behaviour of laser beam welded thin sheet Ti6AI4V was examined in this project as the lifetime of the LVAD impeller has been seen to be limited by fatigue cracking. Grain size, phase content, stress ratio and frequency are all affected fatigue fracture behaviour. A transformed Widmanstätten structure in the weld gave the highest fatigue fracture life. A time of 8 hours heat treatment gave the highest fatigue fracture life due to a good-balance between the grain size and phase content; the existence of metastable (3 limits the crack propagation as well. The geometries, distortion and porosity of the welds were variable and depended on the types of the laser used for the welding process. These factors significantly affected the local stress levels during the tensile testing and fatigue testing. FEA was used to understand and evaluate these influences. By simulation in FEA, the maximum stress locations were observed to be strongly dependent on the specifics of the crosssectional geometries of the welds. For the pulsed Nd: YAG weld in the fatigue testing, the FEA-derived modified local stress amplitudes exhibited a increase of about 40% compared to the nominal applied stress.